Albumin-assisted exfoliated ultrathin rhenium disulfide nanosheets as a tumor targeting and dual-stimuli-responsive drug delivery system for a combination chemo-photothermal treatment. Issue 9 (25th January 2018) - Huang, Qunlian; Wang, Shurong; Zhou, Jie; Zhong, Xiaoyan; Huang, Yilan
Abstract : The resveratrol and folic acid loaded ultrathin rhenium disulfide nanosheet (utReS2 @RSV–FA) could be used as a dual-stimuli-responsive drug delivery system and could effectively be used in a combination chemo-photothermal cancer treatment. Abstract : Herein, we prepared an ultrathin rhenium disulfide nanosheet (utReS2 ) through the bovine serum albumin (BSA)-assisted ultrasonic exfoliation method, which showed great biocompatibility and high near-infrared (NIR) absorbance. The large surface specific area and the presence of BSA facilitate a high loading ratio and modification of multifunctional molecules. The low solubility anti-cancer drug resveratrol (RSV) was loaded onto the utReS2 surface to form a biocompatible nanocomposite (utReS2 @RSV). A targeting molecule, folic acid (FA), was then conjugated to the BSA molecule of utReS2 @RSV, resulting in utReS2 @RSV–FA. The utReS2 @RSV–FA exhibited a photothermal effect under an 808 nm laser irradiation. At pH = 6.5, about 16.5% of the RSV molecules was released from utReS2 @RSV–FA over 24 h, while the value reached 55.3% after six cycles of NIR irradiation (5 min, 1 W cm −2 ). In vitro experiments of utReS2 @RSV–FA showed that it had low cytotoxicity and an excellent HepG2 cells targeting effect. Upon pH/temperature dual-stimuli, utReS2 @RSV–FA showed an enhanced cytotoxic effect. In vivo experiments of utReS2 @RSV–FA intravenously injected into tumor-bearing mice showed that at 24 h post-injection, it could actively target and was largely accumulated in tumor tissue. When the injection was further accompanied by three cycles of NIR irradiation for 5 min, once a day, the tumor was efficiently suppressed, without relapse after 30 days. These findings demonstrate that utReS2 @RSV–FA has a remarkable targeting ability while providing a dual-stimuli-responsive drug delivery system, and could effectively be used in a combination chemo-photothermal cancer treatment.